Transport of Charge Carriers along Dislocations in Si and Ge. Issue 17 (17th July 2019) - Kittler, Martin; Reiche, Manfred; Schwartz, Bernhard; Uebensee, Hartmut; Kosina, Hans; Stanojevic, Zlatan; Baumgartner, Oskar; Ortlepp, Thomas
Abstract : Experimental observations and quantum mechanical device simulations point to different electronic properties of dislocations in silicon and germanium. The experimental data suggest a supermetallic behavior of the dislocations in Si and thus the high strain in the dislocation core is thought to cause the confinement of the charge carriers, which leads to the formation of a 1D electron gas along a dislocation (quantum wire). The resulting significant increase in the electron concentration corresponds to a marked increase in the drain current of metal–oxide–semiconductor field‐effect transistor (MOSFET). The specific resistance of an individual dislocation in Ge is about nine orders of magnitude higher than for a dislocation in Si. The experimental measurements of the strain in dislocation cores in Ge are still missing. Based on the band structure data, the generation of a strain equivalent to that of the dislocation cores in Si appears to be very challenging because of the transition from an indirect into a direct semiconductor with about tenfold lower strain levels. The lower strain in the dislocation core in germanium may not support the carrier confinement as proposed for the dislocation core of silicon, and consequently 1D electron gases are not expected to form along the dislocations in Ge. Abstract : Experimental observations and quantum mechanical device simulations point to different electronic properties of the dislocations in Si and Ge. A supermetallic conduction behavior and strain‐induced carrier confinement (1D electron gas) are proved for dislocations in Si. Both are not confirmed for Ge. The carrier confinement results in higher electron concentrations on dislocation cores in Si than on dislocations in Ge.